Promoting cytidine biosynthesis by modulating pyrimidine metabolism and carbon metabolic regulatory networks in Bacillus subtilis - Xiangjun Zhang; Lu Liu; Pilian Niu; Tong Ye; Wei Ding; Xiaobo Wei; Junnan Xu; Haitian Fang; Huiyan Liu (Microbial Cell Factories)
Abstract Background The modification of single or multiple genes via metabolic engineering can lead to the dysregulation of central metabolism and affect bacterial growth and metabolite accumulation. Meanwhile, transcription factor engineering can trigger metabolic network reprogramming at the global or systemic level, redirecting metabolic flux toward the synthetic pathways of target metabolites. In this study, we modulated pyrimidine and carbon-nitrogen metabolism in Bacillus subtilis through transcription factor engineering to promote the synthesis of cytidine, a drug intermediate. Results First, cytidine synthesis was enhanced by knocking out the transcriptional regulator PyrR, which increased the cytidine titer during shake flask fermentation to 0.67 g/L. Second, mutations in the transcriptional regulator catabolite control protein A (CcpA) significantly promoted cytidine synthesis, increasing the shake flask titer to 2.03 g/L. Finally, after culture in a 5 L fermenter, the cytidine titer reached 7.65 g/L, which was 3.77-fold that of shake flask fermentation. Moreover, a cytidine yield and productivity of 0.06 g/g glucose and 0.16 g/L/h, respectively, were achieved. Subsequently, the regulatory mechanisms through which PyrR and CcpA modification affect cytidine biosynthesis were explored through multi-omics analysis. Transcriptome and metabolome analysis revealed that coordinated alterations in carbon, nitrogen, nucleotide, and amino acid metabolism were essential to promote cytidine synthesis. However, the increased cytidine production in recombinant strains was attributed to the enhancement of pyrimidine metabolism, the Phosphotransferase (PTS) system, the tricarboxylic acid (TCA) cycle, the pentose phosphate (PP) pathway, and nitrogen metabolism. Conclusions These results indicate that PyrR knockdown can enhance pyrimidine metabolic pathway and promote cytidine synthesis. CcpA mutation can reprogram the central carbon-nitrogen metabolic network, change the metabolic flow to de novo synthesis pathway of pyrimidine nucleoside, increase the supply of cytidine synthesis precursors and promote the accumulation of cytidine. Overall, regulation of engineered carbon and nitrogen metabolic networks is essential for improving the efficiency of microbial cell factories.